Establishment of First Afebrile Fit Telephone Clinic at Royal Berkshire Hospital, Reading, United Kingdom - Khistriya, Arti; Aldouri, Ahmed; Hagan, Catherine; Hughes, Sarah; Ives, Tammy; Gill, Rati; Banos, Ines; Carey, Georgina (Journal of Pediatric Epilepsy, 2021)
Children presenting with a suspected seizure are recommended to be seen by a specialist for the diagnosis and management of the epilepsies within 2 weeks of presentation. As part of the Royal College of Pediatrics and Child Health Quality Improvement Project, our project aim was to establish a first afebrile fit telephone clinic in line with The National Institute for Health and Care Excellence guidance. Our results showed safety information was poorly provided and retained at the initial consultation and a follow-up telephone call reinforced safety information and provided a point of contact for patients and families to use. The telephone follow-up also resulted in eight direct referrals into an epilepsy clinic. It is hoped the results from this project will act as a stepping stone to setting up a consultant-led first fit clinic.
Keywords: pediatric epilepsy; first afebrile seizure; epilepsy clinic